Universal Newborn Hearing Screening. Five years of experience - Caselhos, Sérgio (2012)
Hearing impairment is the most common congenital abnormality,with a reported prevalence of 1-3/1000 live births. Universal Newborn Hearing Screening (UNHS) provides early detection of hearing loss.This allows early intervention which is critical to prevent the adverse consequences on speech, language and cognitive development. The aim of this study was to analyse data obtained by the UNHS at the Centro Hospitalar do Alto Ave (CHAA) in the period from June 2005 to March 2010.A total of 11033 newborns were screened. In the past three yearsmore than 95% of all newborns were tested. 0,67% of screenednewborns failed the screening, corresponding to 74 children. Ofthese, 45,9% did not have any risk indicators for deafness.The current results show an improvement in the screeningimplementation at our Institution over time. The ocurrence of hearing impairment among children without risk factors at birth reinforces the need for UNHS in newborns.